La securitización del cine en el siglo xx: interpretaciones sobre la cultura y el poder (2020)
Film industries played an important role in the construction of reality. The discourses, means, and strategies used for the development of conflicts respond to dynamics and facilities of their corresponding moment. This article uses an eclectic view to understand how the securitization of cinema influenced the construction of the collective imaginary in the face of international relations of the twentieth century. Accordingly, it is by means of using data collection tools and hermeneutic and interpretative views that the behavior of actors related to war and hostilities, legitimization, propaganda, and the seventh art are analyzed.